Kultura polityczna systemu bezpieczeństwa narodowego - Trejnis, Zenon (Przegląd Strategiczny, 2013)
The political culture of security is an important factor of each national security system. The political culture term as an analytic conception of security issue still has its definition problems. There still exist three types of them: hostility culture discovered by Thomas Hobbes; rivalry culture found by John Locke; friendship and cooperation culture by Immanuel Kant. The transition from hostility security culture to the friendship culture needs: correlations, a sense of common fate and homogeneity.